2017
DOI: 10.1002/2016wr018833
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic response of the water retention curve in unsaturated soils during drainage to acoustic excitations

Abstract: We examined the effects of acoustic excitations on the water retention curve, i.e., the relationship between capillary pressure (PCtrue) and water saturation true(SWtrue) in unsaturated porous media, during drainage. The water retention curves were measured under static and dynamic conditions, where water was withdrawn from a sandbox with three different pumping rates, 12.6, 19.7, and 25.2 mL/s. Excitations with frequencies of 75, 100, 125, and 150 Hz were applied. The acoustic excitations had no effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…Hassanizadeh et al () calculated approximate values of τ , ranging from 3 × 10 4 to 5 × 10 7 Pa s, based on published experimental studies of dynamic capillarity effect. The values of τ in numerical (see Diamantopoulos & Durner, ; Joekar‐Niasar & Hassanizadeh, , for a review) and experimental studies (e.g., Bottero et al, ; Camps‐Roach et al, ; Das & Mirzaei, ; Goel & O'Carroll, ; Lo et al, ; O'Carroll et al, ; Sakaki et al, ) have been mostly within this range. Part of the variation in reported values can be explained by the fact that τ depends on saturation.…”
Section: Introductionmentioning
confidence: 97%
“…Hassanizadeh et al () calculated approximate values of τ , ranging from 3 × 10 4 to 5 × 10 7 Pa s, based on published experimental studies of dynamic capillarity effect. The values of τ in numerical (see Diamantopoulos & Durner, ; Joekar‐Niasar & Hassanizadeh, , for a review) and experimental studies (e.g., Bottero et al, ; Camps‐Roach et al, ; Das & Mirzaei, ; Goel & O'Carroll, ; Lo et al, ; O'Carroll et al, ; Sakaki et al, ) have been mostly within this range. Part of the variation in reported values can be explained by the fact that τ depends on saturation.…”
Section: Introductionmentioning
confidence: 97%
“…Acoustic excitation effects: Regardless of the mainstream reviewed above, some special boundary conditions raised research interests and are worth to be studied. One contribution from Lo, et al [186] navigated the investigations in the dynamic response of soil water retention behaviour to a novel orientation. Instead of exclusively diving into studying hydraulic boundary conditions, Lo, Yang, Hsu, Chen, Yeh and Hilpert [186] applied acoustic excitations to transient drainage tests on Ottawa sand.…”
Section: The Influential Factors In Dynamic Nonequilibrium Effectmentioning
confidence: 99%
“…Camps-Roach et al (2010) suggested that the DCP effect should be considered when the saturation changed rapidly and the effect of wettability on the DCP coefficient should be investigated. Lo et al (2017) found that acoustic excitation also had a notable effect on the DCP coefficient based on their experiment results, while the essential reason was still unclear. Zhuang et al (2017) carried out a series of drainage experiments to quantify the dynamic capillary coefficient, and found that the DCP coefficient varied slightly at moderate level and increased nearly logarithmically with the decrease of saturation.…”
Section: Introductionmentioning
confidence: 99%